Improving Learning Outcomes of Single Materials through PjBL Model Subtance and Mixed Subtances - PURWANINGSIH, SRI WAHYUNI (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims at improving science learning outcomes through the Project Based Learning (PjBL) Model on single substance and mixed substances. The research was Classroom Action Research with designed by Kemmis and Mc.Taggart. The subject of this research were 15 students of five grade of SDN 1 Tlogowatu. The data collection technique of this research were observations and tests. The data analyzed by using descriptive quantitative and descriptive qualitative method. The result show that Project Based Learning (PjBL) model can improve student’s science achievement. Aftter using PjBL, the average the average score increased from 57,06 to 65,88 with the completeness percentage 35% to 65%. In cycle 2, with the improvement by cycle 1, the everage score was 72,35 with the completeness percentage 76%